Dinosaurs - Maccarone, Grace; Courtney, Richard, 1955- (New York Scholastic, 2001)
Simple text and illustrations present different kinds of dinosaurs.
"Cartwheel books."
240
D
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs